CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF THE COURSE OF PURULENT SIALADENITIS AGAINST THE BACKGROUND OF ENDOCRINE PATHOLOGY - Skikevych, M.G.; Voloshyna, L.I.; Starchenko, I.I.; Lokes, К.P.; Avetikov, D.S. (World of Medicine and Biology, 2024)
Sialoadenitis is a fairly common pathology in the practice of dentists and maxillofacial surgeons. In patients with diabetes mellitus, the disease is often diagnosed for the first time in a surgical clinic; sialoadenitis is diagnosed and, in case of decompensation of the endocrine system, a septic state. Acute parotitis with abscess formation was observed in deceased patients. Microscopically: the presence of abundant cellular inflammatory infiltration with a predominance of neutrophilic leukocytes. Inflammatory infiltration spread diffusely to most of the parenchyma, and in places was focal, forming microabscesses. In the thyroid gland, most follicles were enlarged and filled with colloid. Pathomorphological examination of the thyroid gland: macrofollicular colloid goiter. In the presence of background diseases of the endocrine system, such as hyperthyroidism and diabetes mellitus in particular, patients with inflammatory diseases of the salivary gland (sialoadenitis) should be classified as a risk group, since in some cases they require early hospitalization in the maxillofacial surgery department.
Keywords: salivary gland; sialadenitis; endocrine glands; thyroid gland; pancreas; diabetes mellitus; acute purulent inflammation; morphology